Flushing Versus Pushing Technique for Graft Implantation in Descemet Membrane Endothelial Keratoplasty. Issue 5 (May 2020) - Siebelmann, Sebastian; Janetzko, Mona; König, Peter; Scholz, Paula; Matthaei, Mario; Händel, Alexander; Cursiefen, Claus; Bachmann, Björn
Abstract : Purpose: Descemet membrane endothelial keratoplasty (DMEK) has developed into a safe procedure for the replacement of diseased corneal endothelium. However, DMEK still results in a significant donor endothelial cell loss. Here, we compare 2 different graft implantation techniques. Methods: Twenty patients undergoing DMEK, where a DMEK injection cartridge was used to flush the graft into the anterior chamber (G-38635 single-use DMEK-Cartridge; Geuder AG, Heidelberg, Germany; group A), were retrospectively compared with 20 patients, where a standard lens injection cartridge (AT.Smart Cartridge; Carl Zeiss Meditec AG, Jena, Germany; group B) was used to push the graft with a plunger. Outcome parameters were intraoperative orientation of the graft, insertion-to-attachment time, rebubbling rates, and postoperative best spectacle-corrected visual acuity, endothelial cell count, and central corneal thickness after 12 months. The surfaces of both cartridges were evaluated by scanning electron microscopy. Results: In group A, the insertion-to-attachment time was significantly higher ( P = 0.003). Initially, the graft was oriented correctly in 40% of the patients in group A compared with 90% in group B ( P = 0.001). No differences were obtained between both groups regarding central corneal thickness, endothelial cell count or best spectacle-corrected visual acuity, and rebubbling rates after 12 months. Scanning electron microscopy analysis demonstrated a rougher and sharper surface of the shooter of group B. Conclusions: This study shows significant differences between both insertion techniques regarding correct graft orientation directly after graft implantation leading to prolonged insertion-to-attachment time when the graft is flushed instead of pushed into the anterior chamber.